STUDENTS’ LEARNING CREATIVITY PROFILE: A VIEW FROM SCHOOL ACCREDITATION STATUS - Maryani, Ineu (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
Creativity is a person's ability to create something new. Creativity of students need to be cultivated by all of their environment, such as school environment. Schools accreditations status is one of the determinants environment of student creativity. This article aimed to describe the students' learning creativity profile based on their school's accreditation status. To this end, a survey method was applied. A questionnaire of students' learning creativity was deployed through Google Form. Participants in this study were 2nd-grade students of public junior high schools with accreditation status of National Standard School (SSN), A, and B. The results of the study showed a significant average difference in students' ability in dealing with learning problems between SSN- and A-accredited schools. The average ability to deal with learning problems is also significantly different between A- and B-accredited schools. A significant difference was also found in the students' interest in learning creations and ability to develop in learning between SSN- and A-accredited junior high schools. The results of this study could be used as empirical data for research on guidance and counseling programs to develop students' creativity in schools.